Peran KPU Kabupaten Minahasa dalam Pemenuhan Hak Pilih Warga pada Pemilu Tahun 2024 : Berdasarkan Undang-Undang Nomor 7 Tahun 2017 - Paseki, Dicky Janeman; Gerungan, Carlo Aldrin; Sualang, Djoly Alfrits (Lembaga Dakwah dan Pembangunan Masyarakat Universitas Cokroaminoto Yogyakarta (LDPM UCY), 2025)
This study aims to analyze the role of the Minahasa Regency General Election Commission (KPU) in ensuring the fulfillment of Minahasa residents' voting rights in the 2024 General Election (Pemilu) in accordance with Law No. 7 of 2017 concerning General Elections. This study uses a qualitative approach with a descriptive-analytical method that focuses on the implementation of duties, authorities, and challenges faced by the KPU in managing the permanent voter list (DPT), election socialization, and providing accessibility for vulnerable groups. The results of the study indicate that the Minahasa Regency KPU has a strategic role in implementing inclusive election stages through voter education programs, factual verification of voter data, and strengthening equal community participation for all levels of citizens including the disabled. However, the lack of voter understanding and technical challenges in the field require integrated solutions.